RISK BEHAVIOR, HEALTH PROMOTION, AND HYPERTENSION IN PRODUCTIVE COMMUNITIES IN THE UPTD TAPOS DEPOK AREA - Nina, Nina; Rachma Pramudita, Widya; Fathan, Fadhillah; Hera Ramadhani, Alicia; Aranda, Rizky; Blandin Laleda, Miranti; Gian Purnama, Muhammad (HEARTY, 2024)
In 2021 at the Tapos Health Center, out of 9,352 hypertensive patients aged ≥ 15 years, only 1,547 people (16.5%) received standard services. This problem is a serious health challenge because hypertension contributes to the high mortality rate in the region. The purpose of this study is to identify the problem and its causes and provide alternatives to the existing problem. The research design used for this study is descriptive analytical. This research aims to identify problems and their causes and provide alternatives to existing problems. Data collection and observation were carried out offline and then the data was processed using the Matrix Criteria Method. The results obtained for the problem that is the top priority is the low public interest in health promotion. Therefore, alternative problem solving is needed that can increase public interest in participating in health promotion. As a solution, planning sustainable health programs related to hypertension is a top priority to increase public awareness and participation in hypertension prevention. The program includes periodic health checks, counseling, and joint sports activities. It is hoped that through this program, it can overcome the low public interest in health promotion and ultimately help reduce the risk of hypertension and improve overall public health.